Empowering Coastal Communities: Policy and Practice in the Bajo Fishing Community of Soropia, Southeast Sulawesi - Darmin Tuwu (Randwick International of Social Science Journal, 2026)
This study examines the empowerment of the Bajo traditional fishing community in Soropia Subdistrict, Konawe Regency, Southeast Sulawesi, Indonesia. The research aims to analyze the socio-economic conditions of the Bajo community, identify key challenges in the empowerment process, and formulate a context-based empowerment model. A qualitative approach with a case study design was employed to capture in-depth insights into the lived experiences of the community. Data were collected through in-depth interviews, participatory observation, documentation, and focus group discussions involving fishermen, community leaders, women, and local stakeholders. The data were analyzed using an interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that the Bajo community remains highly dependent on traditional fishing activities, with unstable income influenced by seasonal and environmental factors. Structural challenges such as limited access to capital, technology, education, and markets contribute to their socio-economic vulnerability. Existing empowerment programs tend to be top-down and lack sustainability and community participation. However, the study also identifies significant local potentials, including rich marine resources, strong social capital, local ecological knowledge, and the active role of women in household economies. This study argues that effective empowerment requires a holistic and participatory approach that integrates economic, social, cultural, and environmental dimensions. The proposed model emphasizes strengthening local institutions, enhancing human capacity, promoting sustainable resource management, and supporting gender-inclusive development. The study contributes to the literature on coastal community empowerment by offering a contextual and integrative framework applicable to traditional maritime communities.